Implementasi Protokol UDP Pervasive Multi Device untuk Perangkat myRIO Berbasis LabVIEW (Studi Kasus : Security Box) - Octavian Metta Wisnu Wardhana; Rizal Maulana; Wijaya Kurniawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Pervasive computing is one application of ubiquotous computing that is useful to facilitate the computer operation by minimizing the need for human interaction to the computer. While UDP Pervasive Multi Device is a UDP protocol developed using pervasive computing to be able to recognize the identity of other devices without the need for manual settings from the user. In this paper the UDP Pervasive protocol can be implemented on PC and NI myRIO devices using LabVIEW-based programs. UDP protocols are used because they do not require handshaking to reduce delay and smaller data sizes due to the absence of acknowledgment fields and sequence fields. Each device uses dual state machine system design that has function for detecting other devices automatically and as an application of using other devices address. When the program is first executed, the device broadcasts to all devices. Then the device does listening to receive broadcast data or replies from broadcast. When receiving broadcast data or replies then the device checks the duplication of the device and stores it. The device then sends a reply when receiving broadcast or back to listening. By using the same state machine to detect all device, the device can recognize other devices more than one on the same network. The results of the test obtained that all state-based testing succeeded 100%. Discovery time averaging 0.202754 seconds for 1 myRIO and 0.303201 seconds for 2 myRIO. Sending data delay from PC to myRIO not more than 2 second.